Nutritional Evaluation and Phytochemical Profile of Rice Straw and Indigofera zollingeriana Mixture under Different Fermentation Periods - Mariam Mariam; Sulistiani Ussy; Rahmi Nur; Widiastuti Ardiansyah (Jurnal Ternak, 2026)
This study aimed to evaluate the nutritional content and phytochemical profile of a mixture of rice straw and Indigofera zollingeriana at different fermentation periods. The research was conducted in Mamuju Regency using an experimental method with a Completely Randomized Design (CRD) consisting of four treatments and four replications. The treatments included P0 = without fermentation (0 days), P1 = 7 days fermentation, P2 = 14 days fermentation, and P3 = 21 days fermentation. The feed mixture consisted of 70% rice straw and 30% Indigofera zollingeriana. Observed parameters included dry matter (DM), crude protein (CP), crude fiber (CF), crude fat, ash, nitrogen-free extract (NFE), and phytochemical compounds including tannins, saponins, flavonoids, alkaloids, and total phenols. Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s multiple range test. The results showed that fermentation duration significantly affected (P<0.05) the nutritional content and phytochemical profile of the feed mixture. Fermentation for 14 days (P2) resulted in the highest crude protein, flavonoid, saponin, alkaloid, and total phenol contents, as well as the lowest crude fiber and tannin contents compared to other treatments. Crude protein increased from 10.45% in P0 to 15.76% in P2, while crude fiber decreased from 32.56% to 26.15%. Tannin content also decreased from 2.45% to 1.88% after 14 days of fermentation. It can be concluded that 14 days of fermentation is the optimal period to improve the nutritional quality and phytochemical profile of rice straw and Indigofera zollingeriana mixture as ruminant feed.